2014
DOI: 10.4314/sajas.v43i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kosher (Shechita) and conventional slaughter techniques on shear force, drip and cooking loss of beef

Abstract: ________________________________________________________________________________ AbstractThe objective of this study was to evaluate the effects of Kosher (Shechita) and conventional slaughter methods on shear force, drip and cooking losses of beef (m. longissimus dorsi samples) from South African feedlot cattle. Results revealed significantly lower shear force values for meat samples from cattle slaughtered by the Kosher method compared to those from cattle slaughtered by the conventional slaughter method. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Agbeniga et al 33 & Mast et al, 34 findings agreed with this study. However, Nakyinsige et al 8 & Linares et al 11 observed no significant differences between stunned and non-stunned meat.…”
Section: Meat Textural Analysis (Shear Force)supporting
confidence: 91%
“…Agbeniga et al 33 & Mast et al, 34 findings agreed with this study. However, Nakyinsige et al 8 & Linares et al 11 observed no significant differences between stunned and non-stunned meat.…”
Section: Meat Textural Analysis (Shear Force)supporting
confidence: 91%
“…The finding that slaughter method did not affect drip loss, WHC, cooking loss and shear force agree with earlier reports [ 17 , 44 , 45 ]. Overall, the high pH (6.4–6.8), WHC, and low drip loss, a *, b *, and chroma values reported across slaughter methods are a characteristic of a dark firm and dry (DFD) meat [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Kosher slaughtering, a routine procedure in Israel and other countries [ 34 ], offers particular advantages for genetic analysis of BRD. Kosher slaughtering involves two steps: The actual slaughter, and then a close and detailed examination of the lungs of the slaughtered animals for adhesions.…”
Section: Introductionmentioning
confidence: 99%